Application of landscape’s entropy problem for monitoring and evaluating trend of reforestation: a case study of Sa Pa district, Lao Cai province, Vietnam - Thinh, Nguyen An (VNU Journal of Science: Earth and Environmental Sciences, 2011)
Abstract. The paper introduced a landscape’s entropy problem based on Forman’s approach, Shannon entropy and landscape metric for patch, edge and mosaic at forest class level. Forman's approach to the topic of landscape ecology is dominated by reference to descriptive, spatial shape and pattern as well as the effect of landscape pattern on the flows of water, wind and soil.Shannon entropy or "information entropy", in information theory, is considered a synonym for the name of the H function or a probability equation. As an integrated model, the Landscape’s Entropy problem could be used as a powerful tool to test effects of the interrelation between landscape pattern and ecological process in the landscape. We have tried to apply the landscape entropy problem for forestry change monitoring and evaluation in a case study ofSaPa mountainous district which belongs to Lao Cai province. Results of problem are: CA (Core Area) = 33841.33, MPS (Mean Patch Size) = 417.79, PSCoV (Patch Size Coefficient of Variance) = 571.78, PSSD (Patch Size Standard Deviation) = 2388.85, TE (Total Edge) = 777.21, ED (Edge Density) = 22.97, MSI (Mean Shape Index) = 1.62, and AWMSI (Area-Weighted Mean Shape Index) = 4.19. These results show that, inSaPa, under the afforest and reforest activities, restored forest areas reach high ecological effects. In addition, by using cluster analysis, we divided this territory into 3 clustering areas according to the potential of forest development. Keywords: entropy problem, landscape diversity, afforestation, reforestation, hierarchical cluster analysis, Sa Pa district.